Telaah Normatif Kedudukan Dan Kekuatan Pembuktian Tes Deoxyribonucleic Acid Sebagai Alat Bukti Sah Dalam Sistem Pembuktian Hukum Pidana Nasional - Syadid Jiddan Alharun; Tiara Ramadhani; Aldi Prasetiawan Saputra; Aulia Rexana Sitaresmi; Ria Anggraeni Utami (CV. ITTC INDONESIA, 2025)
This research normatively analyzes the position and probative value of Deoxyribonucleic Acid (DNA) Testing within the Indonesian criminal procedure law system. The underlying legal issue is the controversy surrounding DNA testing to establish the validity of a biological child, particularly when linked to specific criminal acts such as adultery or defamation. The method employed is juridical-normative, using a statutory approach and a conceptual approach, focusing on a comprehensive review of Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP) and related criminal provisions. The analysis of Article 184 paragraph (1) of KUHAP indicates that DNA Testing is not explicitly recognized as an evidence, yet it can be categorized as part of Expert Testimony or Documentary Evidence (Visum et Repertum). The probative force of DNA Testing is absolute in determining biological relationships, but within the criminal context, it must comply with the principle of minimum two valid evidence and be supported by the judge's conviction as stipulated in Article 183 of KUHAP. This research concludes that regulatory harmonization is necessary to provide a more specific and stronger standing for DNA Testing, especially in cases involving the determination of identity or biological relationships.